If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -3) + -1(2y + 4) = -6y Reorder the terms: 2(-3 + y) + -1(2y + 4) = -6y (-3 * 2 + y * 2) + -1(2y + 4) = -6y (-6 + 2y) + -1(2y + 4) = -6y Reorder the terms: -6 + 2y + -1(4 + 2y) = -6y -6 + 2y + (4 * -1 + 2y * -1) = -6y -6 + 2y + (-4 + -2y) = -6y Reorder the terms: -6 + -4 + 2y + -2y = -6y Combine like terms: -6 + -4 = -10 -10 + 2y + -2y = -6y Combine like terms: 2y + -2y = 0 -10 + 0 = -6y -10 = -6y Solving -10 = -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. -10 + 6y = -6y + 6y Combine like terms: -6y + 6y = 0 -10 + 6y = 0 Add '10' to each side of the equation. -10 + 10 + 6y = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 6y = 0 + 10 6y = 0 + 10 Combine like terms: 0 + 10 = 10 6y = 10 Divide each side by '6'. y = 1.666666667 Simplifying y = 1.666666667
| .25a+.50b+c=20FindABC | | 5+7x=3-(1+x) | | .25a+.50b+c=20 | | 4x+-3x= | | 182-5x=40x+22 | | 182-5x=40x+27 | | 3x-15=y+36 | | 3x-15=x+36 | | y=(2+4)(3-4) | | 1.4x=0.1x+52 | | x=600-2x^2 | | 4x+2(x+1)=14 | | -4x-(5)=30 | | y=4(.75)-12 | | 3w-2x-y+6w+15x-6y= | | .24=-18z | | 5x-3y+15w-4y-6w+8x= | | y=2lnx-8x | | 6w+8y+5x+8x-15y+3w= | | 4y-12=2y+40 | | -3(4)+y=-5 | | 2x+10=10x-48 | | 85-3x=8+19 | | 0=8-24x-12x^2 | | 10x+18y=12 | | 5(8-3x)=55 | | 3(2x+7)-4=7-5(4-3x) | | x^2+32x+128=0 | | X^2-2(x-2)020=20 | | 2x+11=-33-x | | [n-1]*4=28 | | x^2+-2x+2=0 |